The acceleration of garlic (Allium sativum L) ethanolic extract on gingival wound healing process in Wistar rats - Indra Bramanti; . Ngatidjan; Setyo Purwono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Garlic (Allium sativum L) is a medicinal plant traditionally used to relieve pain. Garlic’s active constituents, allicin and triacremonone, have been proven to have antibacterial and antiinflammatory activity. The aim of this study was to investigate the effect of garlic ethanolic extract gel in gingival wound healing process of rats. Thirty male Wistar rats aged 10 weeks with with body weight 200-250 g were subjected in this study. Rats were divided randomly into five groups with six rats in each group. Group I as negative control was given sodium carboxymethyl cellulose (Na CMC) base gel. Group II as positive control was given Benzydamine® gel and Group IV-V were given garlic ethanolic extract gel at dose of 20, 40 and 80%, respectively. Each group was subdivided into two sub groups of three rats according to the decapitation period which were 5th (D-5) and 7th (D-7) day after the garlic extract gel application. Excisional wounds using punch biopsy, 2.5 mm in diameter, were created at the mandibular labial gingiva between right and left incisor teeth of the rats. The garlic extract gel of each preparation dose was then applied on the wound three times a day, starting at 0 day until 7th day. The decapitation was conducted on the D-5 and D-7. Histological slides of wounded tissue were prepared. Epithelial thickness, new blood vessel, and number of fibroblast were examined. The results showed that the epithelial thickness of garlic ethanolic extract gel groups was significantly higher than control group (p<0.05), especially after 5thday application. However, the number of new blood vessels and the amount of fibroblast of those groups were not significantly higher than control group (p>0.05). In conclusion, topical application of garlic ethanolic extract gel accelerates the gingival wound healing process in rats by increasing epithelial thickness.